Resistance of Galla and Small East African goats in the sub-humid tropics to gastrointestinal nematode infections and the peri-parturient rise in faecal egg counts - Baker, R.L.; Mwamachi, D.M.; Audho, James O.; Aduda, Eric O.; Thorpe, W.R. (Elsevier, 1998)
A study was carried out from 1994 to 1996 to compare the resistance to naturally acquired gastrointestinal (GI) nematode infections (predominantly Haemonchus contortus) of 88 Galla and 114 Small East Africa (SEA) goats (does) in the sub-humid coastal region of Kenya. Live weights (LWT), blood packed cell volume (PCV) and faecal egg counts (FEC) were recordeed each year at mating, 3-4 months after mating, 1-2 weeks before kidding and 1-4 months after kidding. There was a significant increase in FEC and a decline in PCV in lactaing does compared to non-lactating does over the peri-parturient period. This peri-parturient rise in FEC occurred in both breeds but was more marked and persistent in the Galla than in the SEA. The SEA does were more resistant to GI nematode infections than Galla does as shown by their significantly lower FEC and higher PCV at all sampling times over the reproductive cycle, but this breed difference was particularly marked over the lactation period.